PEMBELAJARAN APRESIASI DRAMA SISWA KELAS XI SMA NEGERI 16 BANDAR LAMPUNG - Ayu Purnamasari; Ni Nyoman Wetty Suliani; Mulyanto Widodo (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem presented in this research was how is the learning process of drama appreciation at the eleven grade students of SMAN 16 Bandar Lampung in academic year of 2012/2013. Based on the problem above, the objective of this research was to describe the learning process of drama appreciation including planning, implementation, and evaluation of drama appreciation. Based on this research, lesson plans designed by teachers already meet the criteria specified lesson plan. However, there are still shortcomings in the formulation of learning objectives and time allocation. Implementation of learning that form of teacher activity in the classroom consists of preliminary activities, core activities, and closing activities. Students activities in implementation of learning drama appreciation consists of visual activity, verbal activity, the activity of listening, moving activity, mental activity and emotional activity. Assessment of student learning outcomes is conducted by the teacher performance appraisal or deed.Masalah dalam penelitian ini adalah bagaimanakah proses pembelajaran apresiasi drama siswa kelas XI SMA Negeri 16 Bandar Lampung tahun pelajaran 2012/2013. Penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran apresiasi drama meliputi perencanaan, pelaksanaan, dan evaluasi pembelajaran apresiasi drama. Berdasarkan hasil penelitian, perencanaan pembelajaran yang dirancang oleh guru sudah memenuhi kriteria Rencana Pelaksanaan Pembelajaran yang ditentukan. Namun, masih terdapat kekurangan pada perumusan tujuan pembelajaran dan alokasi waktunya. Pelaksanaan pembelajaran yang berupa aktivitas guru dalam kelas terdiri atas kegiatan pendahuluan, kegiatan inti, dan kegiatan penutup. Aktivitas siswa dalam pelaksanaan pembelajaran apresiasi drama terdiri atas aktivitas visual, aktivitas lisan, aktivitas mendengarkan, aktivitas bergerak, aktivitas mental, dan aktivitas emosi. Penilaian hasil belajar siswa yang dilakukan oleh guru ialah penilaian perbuatan atau unjuk kerja.Kata kunci: apresiasi, drama, pembelajaran.